STUDY OF THE DISSOLUTION BEHAVIOR OF NICKEL, COBALT, IRON, AND MAGNESIUM FROM LIMONITIC NICKEL ORES AS A FUNCTION OF TEMPERATURE AT ATMOSPHERIC AND HIGH PRESSURE - Annisa, Nur
Nickel is a transition metal that has widespread applications, one of them being as a component in the production of vehicle electric batteries that can be obtained through hydrometallurgical processing. Indonesia is one of the countries with the largest nickel reserve and nickel ore as nickel laterite ore. Technology processing lateritic nickel ore among them that is through leaching in sulphuric acid (H2SO4) processes such as high-pressure acid leaching (HPAL) and atmospheric agitation leaching (AL) processes. Iron is the main impurity element in nickel limonite ore that comes dissolved during the leaching process. This research was done to study the dissolution and precipitation behavior of nickel, cobalt, iron, and magnesium on limonite ore from Halmahera Island, Indonesia, for HPAL and AL processes in H2SO4 solution.